EcoGreenRoof – EGR: Eco-materials Development for Green Roofs - Pinheiro, Vânia (2019)
The project EcoGreenRoofs - EGR aims to develop ecological substrates for application in green roofs, which include in their formulation industrial waste of organic and inorganic base. The substrates are tentatively produced exclusively from industrial waste and / or materials derived from waste treated, and tested at a facility to be studied, developed and built on pilot scale. The substrates produced will be tested under real conditions for their validation and inherent production process. This project aims also to evaluate the commercialization of substrates by analyzing the technical, economic and environmental components. The project is being carried out in co-promotion by two enterprises, one with know-how in the execution of green roofs (Neoturf) and the other with knowledge to implementation of industrial solutions aiming waste management (W2V), and by two SI & I entities with the knowledge and means to develop waste recovery studies (CVR) and roof solutions (Itecons).